2007
DOI: 10.1002/cmdc.200700066
|View full text |Cite
|
Sign up to set email alerts
|

Oxime and Oxime Ether Derivatives of 1,4‐Benzothiazine Related to Oxiconazole

Abstract: The synthesis, in vitro antifungal activity, and molecular docking experiments of some oxime and oxime ether derivatives of azole 1,4-benzothiazine are reported herein, with the aim of evaluating the influence of a partially constrained scaffold that is structurally related to Oxiconazole and bearing the 1,4-benzothiazine moiety, on the inhibition of Candida albicans CYP51.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…(2002) (Polak, 1982). Several compounds containing an oxime or an oxime ether function have been reported to exhibit antimicrobial activity (Porretta et al, 1993;Baji et al, 1995;Rossello et al, 2002;Emami et al, 2002;Emami et al, 2004;Ramalingan et al, 2006;Milanese et al, 2007;Bhandari et al, 2009). In our earlier studies, we reported X-ray structures of benzimidazole substituted oxiconazole derivatives (Özel Güven et al, 2007a;Özel Güven et al, 2009a;Özel Güven et al, 2009b).…”
Section: Crystal Datamentioning
confidence: 94%
See 1 more Smart Citation
“…(2002) (Polak, 1982). Several compounds containing an oxime or an oxime ether function have been reported to exhibit antimicrobial activity (Porretta et al, 1993;Baji et al, 1995;Rossello et al, 2002;Emami et al, 2002;Emami et al, 2004;Ramalingan et al, 2006;Milanese et al, 2007;Bhandari et al, 2009). In our earlier studies, we reported X-ray structures of benzimidazole substituted oxiconazole derivatives (Özel Güven et al, 2007a;Özel Güven et al, 2009a;Özel Güven et al, 2009b).…”
Section: Crystal Datamentioning
confidence: 94%
“…For general background to oximes and oxime ethers and their biological activity, see: Baji et al (1995); Bhandari et al (2009); Emami et al (2002Emami et al ( , 2004; Milanese et al (2007); Polak (1982); Porretta et al (1993); Ramalingan et al (2006); Rossello et al (2002). For related structures, see: Ö zel Gü ven et al (2007aGü ven et al ( ,b, 2009a.…”
Section: Related Literaturementioning
confidence: 99%
“…Oxiconazole is a well established drug for treatment of many mycotic infections, having an oxime group (Polak, 1982). Several compounds containing an oxime or an oxime ether function have been reported to exhibit antimicrobial activity (Poretta et al, 1993;Baji et al, 1995;Rosello et al, 2002;Emami et al, 2002;Emami et al, 2004;Ramalingan et al, 2006;Milanese et al, 2007;Bhandari et al, 2009). In our earlier studies, we reported X-ray structures of benzimidazole substituted oxiconazole derivatives (Özel Güven et al, 2007a;2007b;.…”
Section: Data Collectionmentioning
confidence: 99%
“…For general background to oximes and oxime ethers, including their biological activity, see: Baji et al (1995); Bhandari et al (2009); Emami et al (2002Emami et al ( , 2004; Milanese et al (2007); Polak (1982); Poretta et al (1993); Ramalingan et al (2006); Rosello et al (2002). For related structures, see: Ö zel Gü ven et al (2007aGü ven et al ( ,b, 2009.…”
Section: Related Literaturementioning
confidence: 99%
“…Despite these challenges, various attempts have been made in order to obtain benzothiazine derivatives 23, 24 with higher antifungal properties 72, 73. Some derivatives have shown marginal antifungal activities 74; however, oximes of 1,4‐benzothiazine 43 and oxime ether derivatives of azoles 1,4‐benzothiazine 44 were reported to have moderate inhibitory effect on Candida albicans CYP51 75 while compound 45 (where R = Bu) even competed favorably with the fluconazole reference drug at MIC values <1.8 µg/mL against Candida albicans and Candida krusei 76.…”
Section: Pharmacologymentioning
confidence: 99%